2012
DOI: 10.4304/jltr.3.1.23-29
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Formal Language Learning Environment on Vocabulary Learning Strategies

Abstract: Abstract-This study investigates ESL students studying in the programIndex Terms-formal language learning environment, vocabulary learning strategies, ESL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Motivation not only within oneself, but from the surrounding also has a great impact on the process of English language learning. In a study done by Kamali, Mostapha and Baki (2012) found the role of peers, teachers, and environment of classroom influenced the use of vocabulary learning strategies among Malaysian ESL students. Supportive and unsupportive parents also could affect learners (Asgari and Mustapha, 2011).…”
Section: Barriers To Vocabulary Learningmentioning
confidence: 99%
“…Motivation not only within oneself, but from the surrounding also has a great impact on the process of English language learning. In a study done by Kamali, Mostapha and Baki (2012) found the role of peers, teachers, and environment of classroom influenced the use of vocabulary learning strategies among Malaysian ESL students. Supportive and unsupportive parents also could affect learners (Asgari and Mustapha, 2011).…”
Section: Barriers To Vocabulary Learningmentioning
confidence: 99%
“…On the other hand, Kameli et al (2012) studied the impact of a formal language learning setting (classroom, teachers, and peers) on vocabulary acquisition techniques among ESL students enrolled in the Universiti Putra Malaysia's Teaching English as a Second Language (TESL) programme (UPM). This study focused on explaining how vocabulary learning strategies of ESL students were interfered with the school environments and mediating agents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Focusing on a distinctive aspect of autonomous learning research within a formal postsecondary setting, Kameli et al (2012) examined the impact of several factors on Malaysian university EFL students' vocabulary learning strategies. Among the most significant of these factors were the degree to which the teacher encouraged student learning, the amount of peer-review support, and the method of teaching.…”
Section: Fostering Autonomy In Vocabulary Developmentmentioning
confidence: 99%
“…Learner autonomy is defined as a learner's willingness to take taking responsibility for participating, applying, monitoring, and evaluating his/her learning, which is usually developed with the support of a teacher. Research has shown that learner autonomy is the key for vocabulary development (Dogan and Mirici, 2017;Hu and Zhang, 2017;Kameli et al, 2012;Kristmanson et al, 2013;Li, 2015;Phan and Hamid, 2017;Tuan, 2011). The idea of fostering autonomy in vocabulary development for English as a foreign language (EFL) students has not been widely implemented in the field of education in the Kingdom of Saudi Arabia (KSA) (Almusharraf, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation